Assessment of the role of the Edinburgh dysphagia score in referral triage in a national service evaluation of the urgent suspected upper gastrointestinal cancer pathway. Issue 9 (5th March 2022) - Kamran, Umair; King, Dominic; Banks, Matthew; Nylander, David; Shetty, Sharan; Hebbar, Srisha; Ransford, Rupert; Mitchell, David; Williams, Matthew; Gupta, Sanjay; Cheung, Danny; Baker, Graham; et al.
Summary: Background: The British Society of Gastroenterology has recommended the Edinburgh Dysphagia Score (EDS) to risk‐stratify dysphagia referrals during the endoscopy COVID recovery phase. Aims: External validation of the diagnostic accuracy of EDS and exploration of potential changes to improve its diagnostic performance. Methods: A prospective multicentre study of consecutive patients referred with dysphagia on an urgent suspected upper gastrointestinal (UGI) cancer pathway between May 2020 and February 2021. The sensitivity and negative predictive value (NPV) of EDS were calculated. Variables associated with UGI cancer were identified by forward stepwise logistic regression and a modified Cancer Dysphagia Score (CDS) developed. Results: 1301 patients were included from 19 endoscopy providers; 43% male; median age 62 (IQR 51–73) years. 91 (7%) UGI cancers were diagnosed, including 80 oesophageal, 10 gastric and one duodenal cancer. An EDS ≥3.5 had a sensitivity of 96.7 (95% CI 90.7–99.3)% and an NPV of 99.3 (97.8–99.8)%. Age, male sex, progressive dysphagia and unintentional weight loss >3 kg were positively associated and acid reflux and localisation to the neck were negatively associated with UGI cancer. Dysphagia duration <6 months utilised in EDS was replaced with progressive dysphagia in CDS. CDS ≥5.5 had a sensitivity of 97.8 (92.3–99.7)% and NPV of 99.5 (98.1–99.9)%. Area under receiver operating curve was 0.83 for CDS, compared to 0.81 for EDS. Conclusions: In a national cohort, the EDS has high sensitivity and NPV as a triage tool for UGI cancer. The CDS offers even higher diagnostic accuracy. The EDS or CDS should be incorporated into the urgent suspected UGI cancer pathway. Abstract : In a national cohort of patients referred with dysphagia, an updated Cancer Dysphagia Score offered higher diagnostic accuracy as a triage tool for upper gastrointestinal (UGI) cancer than Edinburgh Dysphagia Score, especially for younger patients. These scoring systems should be validated in primary care and incorporated into the urgent UGI cancer pathway.